Saberes ancestrales para la siembra y cosecha de agua de uso agrícola en el Ecuador - Rodríguez Ramos, Stalin Joel (2022)
Sowing and harvesting water for agricultural use is identified through which man or woman collects and infiltrates (sows) rainwater, surface runoff, hypodermic and groundwater into the subsoil in order to be able to recover (harvest) it sometime later. Planting and harvesting water provides farmers with water for crops, animals and household chores in times of drought. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose that the reader learns about the ancestral knowledge for the sowing and harvesting of water for agricultural use in Ecuador. From the above detailed, it was determined that water harvesting has a first order potential to improve the provision and seasonal regulation of water for social, productive and environmental use (improvement of wetlands), in the same territory of water supply or in nearby regions. Water planting and harvesting allows understanding several simple and less expensive techniques to capture and conserve rainwater to be used for agricultural activities and domestic chores, especially in localities that lack water for these functions. The planting and harvesting of water is carried out through the construction of infiltration ditches, qochas, conservation and healing of pastures, as well as afforestation and reforestation. The idea is to gather for low water levels. There are several strategies and practices to plant and harvest rainwater, to cope with its regional storage and to use it sooner or later in positive places, in positive instances and in safe quantities.